IMPLEMENTASI GREEN BANKING PADA LAYANAN PERBANKAN SYARIAH DALAM MEWUJUDKAN KEUANGAN KEBERLANJUTAN (SUSTAINABLE FINANCE) - Imelda, Eza; Fasa, Muhammad Iqbal (Noble Cendekia Indonesia, 2025)
Humans must adopt ecologically friendly practices due to the growing number of environmental damage cases and population growth, particularly in the industrial sector. The purpose of this study is to investigate how Islamic banking services can use green banking to develop sustainable finance. Using secondary data from a literature review, this study employs a qualitative methodology. Because banks that employ financing for environmentally beneficial initiatives as a business strategy have a greater competitive advantage, the study's findings suggest that Islamic banks do not want the projects they sponsor to degrade the environment to the point of igniting public unrest.